Dynamic mechanical response and deformation-induced co-axial nanocrystalline grains facilitating crack formation in magnesium-yttrium alloy - Shuang Yang; Fei Liu; Fei Chen; Yuan-Biao Tan; Hao Fu; Si-Yuan Wei; Song Xiang (Journal of Magnesium and Alloys)
The dynamic mechanical response and deformation mechanism of magnesium-yttrium alloy at high strain rate were investigated using split-Hopkinson pressure bar (SHPB) impact, and the microstructure evolution and crack formation mechanism were revealed. The yield strength and work hardening rate increase significantly with increasing impact strain rate. Deformation twinning and non-basal dislocation slip are the primary deformation mechanisms during testing. Contrary to crack initiation mechanism facilitated by adiabatic shear bands, we find that high-density co-axial nanocrystalline grains form near cracks, which leads to local softening and promotes crack initiation and rapid propagation. Most grains have similar 〈1¯21¯0〉 orientations, with unique misorientation of 24°, 32°, 62°, 78° and 90° between adjacent grains, suggesting that these grains are primarily formed by interface transformation, which exhibits distinct differences from recrystallized grains. Our results shed light upon the dynamic mechanical response and crack formation mechanism in magnesium alloys under impact deformation.